Disruption of NF‐κB1 prevents bone loss caused by mechanical unloading. (21st May 2013) - Nakamura, Hitomi; Aoki, Kazuhiro; Masuda, Wataru; Alles, Neil; Nagano, Kenichi; Fukushima, Hidefumi; Osawa, Kenji; Yasuda, Hisataka; Nakamura, Ichiro; Mikuni‐Takagaki, Yuko; Ohya, Keiichi; Maki, Kenshi; et al.
ABSTRACT Mechanical unloading, such as in a microgravity environment in space or during bed rest (for patients who require prolonged bed rest), leads to a decrease in bone mass because of the suppression of bone formation and the stimulation of bone resorption. To address the challenges presented by a prolonged stay in space and the forthcoming era of a super‐aged society, it will be important to prevent the bone loss caused by prolonged mechanical unloading. Nuclear factor κB (NF‐κB) transcription factors are activated by mechanical loading and inflammatory cytokines. Our objective was to elucidate the role of NF‐κB pathways in bone loss that are caused by mechanical unloading. Eight‐week‐old wild‐type (WT) and NF‐κB1‐deficient mice were randomly assigned to a control or mechanically unloaded with tail suspension group. After 2 weeks, a radiographic analysis indicated a decrease in bone mass in the tibias and femurs of the unloaded WT mice but not in the NF‐κB1–deficient mice. An NF‐κB1 deficiency suppressed the unloading‐induced reduction in bone formation by maintaining the proportion and/or potential of osteoprogenitors or immature osteoblasts, and by suppression of bone resorption through the inhibition of intracellular signaling through the receptor activator of NF‐κB ligand (RANKL) in osteoclast precursors. Thus, NF‐κB1 is involved in two aspects of rapid reduction in bone mass that are induced by disuse osteoporosis in space or bed rest.